2021
DOI: 10.1038/d41573-021-00202-8
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two antiviral targets — and the COVID-19 drugs that bind them

Abstract: A tale of two antiviral targets -and the COVID-19 drugs that bind themThe FDA is considering authorizations for Pfizer's paxlovid and Merck & Co.'s molnupiravir, the first two oral COVID-19 antivirals.COVID-19, for all of the problems it has created, has shown the unprecedented speed with which drug developers can move. Vaccines and bespoke antibodies were among the first responders on the COVID-19 scene, authorized just under 11 months from the release of the SARS-CoV-2 sequence. Now oral antivirals, from Pfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
131
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(132 citation statements)
references
References 0 publications
1
131
0
Order By: Relevance
“…Signals for the calculated 1 H NMR spectra of the ground states of the optimized structures of the keto-oxime, keto-hydroxylamine, and hydroxyl-oxime tautomers of molnupiravir, obtained by using the DFT/GIAO/B3LYP/6-311++G(2d,p) method (see Figure 3 for atoms labelling). Molnupiravir is known to be mutagenic [30]. Interestingly, using the OSIRIS Property Explorer software [31], we have established that while the keto-hydroxylamine tautomer is indeed mutagenic, its keto-oxime and hydroxyl-oxime derivatives do not possess mutagenic properties.…”
Section: Resultsmentioning
confidence: 96%
“…Signals for the calculated 1 H NMR spectra of the ground states of the optimized structures of the keto-oxime, keto-hydroxylamine, and hydroxyl-oxime tautomers of molnupiravir, obtained by using the DFT/GIAO/B3LYP/6-311++G(2d,p) method (see Figure 3 for atoms labelling). Molnupiravir is known to be mutagenic [30]. Interestingly, using the OSIRIS Property Explorer software [31], we have established that while the keto-hydroxylamine tautomer is indeed mutagenic, its keto-oxime and hydroxyl-oxime derivatives do not possess mutagenic properties.…”
Section: Resultsmentioning
confidence: 96%
“…Recently, EUAs for Paxlovid, molnupiravir, and remdesivir were issued, which should help facilitate antiviral drug therapy for COVID-19 [ 20 , 38 , 39 ]. Paxlovid is a main protease (Mpro) inhibitor that has been shown to reduce hospitalization or death by 89% when administered within 3 days of symptom onset; molnupiravir incorporates the wrong bases into new viral RNA, and has been shown to reduce hospitalization or death by 30% when administered within 5 days of symptom onset, while remdesivir is a nucleotide prodrug of an adenosine analog that has been shown to reduce time to clinical improvement [ 40 ]. The oral antivirals (Paxlovid and molnupiravir) can be used in non-hospitalized patients, raising the hopes for COVID-19 treatments, but there is room for improvement of the drug repertoire, as antiviral drugs are not always efficacious, owing to viral resistance.…”
Section: Respiratory Virusesmentioning
confidence: 99%
“…Molnupiravir originated from George Painter’s laboratory and Drug Innovations at Emory University [ 17 ]. In 2013, efforts were made to develop a broad-acting antiviral for RNA-encoded viruses, including highly pathogenic coronaviruses and influenza viruses, as well as encephalitic alphaviruses such as Venezuelan, Eastern, and Western equine encephalitis viruses.…”
mentioning
confidence: 99%
“…On 30 November 2021, an FDA advisory committee voted narrowly—13 to 10—in favor of an EUA for molnupiravir. Phase III results from 1433 patients showed that the drug reduced hospitalization or death by 30% when it was administered within five days of symptom onset, while interim results of Phase II/III data from the ongoing MOVe-OUT trial showed a 48% reduction [ 17 , 23 ]. The study included patients recruited from multiple countries with risk factors of poor disease outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation